2015
DOI: 10.1109/tpel.2014.2378731
|View full text |Cite
|
Sign up to set email alerts
|

Small-Signal Stability Analysis of Three-Phase AC Systems in the Presence of Constant Power Loads Based on Measured d-q Frame Impedances

Abstract: Small-signal stability is of great concern for electrical power systems with a large number of regulated power converters. In the case of dc systems, stability can be predicted by examining the locus described by the ratio of the source and load impedances in the complex plane per the Nyquist stability criterion. For balanced three-phase ac systems the same impedance-based method applies, for which this paper uses impedances in the synchronous rotating reference (d-q) frame. Small-signal stability can be deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
190
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 384 publications
(199 citation statements)
references
References 35 publications
4
190
0
5
Order By: Relevance
“…The only notable difference is seen in the positive sequence impedance between 20 and 40 Hz. The model in (1) gives identical result as the reduced model (18), and this is expected since their analytic expressions are the same. The accurate model (16) gives identical results as the model obtained by the two frequency sweeps.…”
Section: Equivalence Validationmentioning
confidence: 63%
See 4 more Smart Citations
“…The only notable difference is seen in the positive sequence impedance between 20 and 40 Hz. The model in (1) gives identical result as the reduced model (18), and this is expected since their analytic expressions are the same. The accurate model (16) gives identical results as the model obtained by the two frequency sweeps.…”
Section: Equivalence Validationmentioning
confidence: 63%
“…By visual inspection it is concluded that these two expressions complies with (18). The only exception is the argument of the filter transfer functions G v (s) and G i (s), this is due to the different modeling discussed in section II-B and appendix B.…”
Section: Relation Between Impedance Models In Original and Modifimentioning
confidence: 72%
See 3 more Smart Citations